Efficacy and safety of cadonilimab (PD-1/CTLA-4 bispecific) in combination with chemotherapy in anti-PD-1-resistant recurrent or metastatic nasopharyngeal carcinoma: a single-arm, open-label, phase 2 trial - Yaofei Jiang; Weixin Bei; Lin Wang; Nian Lu; Cheng Xu; Hu Liang; Liangru Ke; Yanfang Ye; Shuiqing He; Shuhui Dong; Qin Liu; Chuanrun Zhang; et al. (BMC Medicine)
Abstract Background We aimed to evaluate the efficacy and safety of cadonilimab (anti-PD-1 and CTLA-4 bispecific antibody) plus TPC chemotherapy (NAB-paclitaxel, cisplatin or lobaplatin, and capecitabine) in patients with recurrent or metastatic nasopharyngeal carcinoma (RM-NPC) who failed to PD-1 inhibitor-containing regimens. Methods In this single-arm, open-label, phase 2 study, RM-NPC patients who failed to at least one line of systemic chemotherapy and anti-PD-1 immunotherapy were enrolled and received cadonilimab plus TPC chemotherapy every 3 weeks for up to 6 cycles, followed by cadonilimab plus capecitabine every 3 weeks for a maximum of 2 years. The primary endpoint was the objective response rate (ORR). The secondary endpoints included progression-free survival (PFS), overall survival (OS), duration of response (DoR), and safety. Results Twenty-five patients were enrolled (84% male; median age 44 years (range, 24–60)), with a median follow-up of 10.2 months. The ORR was 68%, with 3 complete responses, 14 partial responses, and 6 stable diseases. The median DoR was 9.1 months (95% CI, 3.8–14.5 months). The median PFS was 10.6 months (95% CI, 5.2–16.0 months). The 12-month OS was 75.6%. Treatment was well tolerated. Grade 3 or 4 treatment-related adverse events occurred in 12 (48%) patients. Fourteen patients (56%) experienced potentially immune-related adverse events (irAEs). One patient experienced a grade 3 immune-related rash and another patient had grade 3 immune-related lipase increased. No treatment-related death occurred. Conclusions Cadonilimab in combination with TPC chemotherapy demonstrated promising antitumoral efficacy and manageable toxicities in patients with RM-NPC who failed frontline immunotherapy. Further trials are warranted to confirm and expand these findings. Trial registration This trial was registered at chictr.org.cn (ChiCTR2200067057).